Technology acceptance in organizations - Stewart, Laurie (Kansas State University, 2013)
New technology has changed how people do business. With rapid development of technology, it has been difficult for businesses and organizations to successfully implement technology advancements. This problem has spurred research in the area of technology acceptance. The Technology Acceptance Model (Davis, 1989) is a dominant theory used to explain technology use. Although many researchers have copied, expanded, and altered this model through quantitative research, making it robust, this study will further the model by using qualitative methods to explore how members understand and classify technology use. This study adds to the existing knowledge of computer-mediated communication and technology acceptance by exploring information technology use within a volunteer or not-for-profit organization (NPO). In order to offer a unique perspective to exploring how organizational members understand and adopt new technology, this study employs qualitative methodology to a topic traditionally explored through quantitative surveys and measurements. Research questions specifically consider why organizational members accept or reject new technology and how organizational membership affects technology acceptance. Using the third iteration of the technology acceptance model (TAM 3), data confirm perceived usefulness and perceived ease as determinants of technology acceptance. The influencing factors of perceived usefulness and perceived ease of use were also confirmed. Two new influencing factors of perceived usefulness emerged in this study: appropriateness and information overload. Also, insight into the role of age and technology adoption calls into question stereotypical misconceptions of technology use and acceptance. Overall, this study confirms and expands on research in the area of technology acceptance.
Keywords: Technology acceptance; Communication (0459)